Bukan hanya sekedar angka: memahami peran matematika dalam kehidupan nyata - rustama, yuniar dwi (Maliki Interdisciplinary Journal, 2025)
Mathematics is not just a science related to numbers and formulas, but it also plays an important role in many aspects of daily life. This article outlines how mathematical concepts are implemented in real-life activities such as personal finance management, budgeting, architectural design, decision-making, as well as technology development and innovation. Not only that, mathematics also contributes to the formation of critical, systematic, and analytical thinking that is very useful in problem-solving and facing the challenges of modern life. This research emphasizes the importance of a contextual and applicative approach to learning mathematics, so that students can and are able to connect the material with the realities they face. Thus, mathematics is not only an academic medium but also an important life skill to enhance the quality and effectiveness of decision-making and problem-solving.